Antioxidants Distribution in Pulp and Seeds of Black and Red Goji Berries as Affected by Boiling Processing. (24th October 2017) - Xin, Guang; Zhu, Fengmei; Du, Bin; Xu, Baojun
Abstract : Pulp and seeds from four varieties of black goji and two varieties of red goji with different geographical origins were examined for their total phenolic content (TPC), total flavonoid content (TFC), condensed tannin content (CTT), monomeric anthocyanin content (MAC), 2, 2-diphenyl-1-picrylhydrazyl (DPPH) scavenging capacity, and ferric reducing antioxidant power (FRAP) using colorimetric methods. Contribution rates of pulp and seed to phytochemical contents and overall antioxidant capacities of whole fruits were calculated for each parameter. It was observed that most of the phytochemicals and antioxidant activities were predominantly contributed by the pulp in all six varieties. Boiling led to significant ( p < 0.05) losses in the phytochemical content and antioxidant capacity. The average MAC value in black goji was significantly ( p < 0.05) higher than that observed for red goji.